Surface Runoff Analysis Using SCS-CN Method in Summarecon Serpong Area - Cantik, Bella Koes Paulina; Sapan, Elenora Gita Alamanda; Ghiffari, Muhammad Razzaaq Al; Yuvhendmindo, Muhammad Ravi; Aziz, Muhammad Luthfi (Universitas Negeri Yogyakarta, 2022)
The increasing population is definitely in line with the rising demand for housing. One area with many residents is Tangerang Regency, Banten with a population growth rate of 5,85% per year. PT. Summarecon Agung Tbk. becomes one of the developers of an integrated area in Tangerang Regency in fulfilling housing's need. However, the wider the development of an area, it is parallel with the changes in land cover that significantly impact surface runoff. Therefore, this study aims to determine the surface runoff in the Summarecon Serpong area. The research method used is the Secondary Data Analysis (SDA) approach which requires several data; rainfall, land cover, and soil type. These data were then processed using Frequency Analysis to obtain design rainfall and continued to the SCS-CN Method to obtain surface runoff with the return period at 2 years, 5 years, 10 years, 20 years, and 100 years. The land cover in the Summarecon Serpong area was dominated by buildings, with the Hydrologic Soil Groups (KHT) in the form of Groups C and D. The calculation of the Composite Curve Number (CNk) value based on land cover and Hydrologic Soil Groups were 88,89, while the calculation of direct runoff using the SCS CN Method with a return period of 2 years, 5 years, 10 years, 20 years, and 100 years respectively were 77 mm, 121 mm, 154 mm, 188 mm, and 275 mm. The lowest surface runoff occurred on land cover in the form of green open land with Hydrologic Soil Group C, and the highest surface runoff occurred on land cover in the form of water bodies. This analysis indicates that focusing on the green open land in the Summarecon Serpong area can reduce surface runoff while increasing infiltration to maintain the sustainability hydrologic system.